Reproducibility of peak oxygen consumption and the impact of test variability on classification of individual training responses in young recreationally active adults. (28th September 2017) - Edgett, Brittany A.; Bonafiglia, Jacob T.; Raleigh, James P.; Rotundo, Mario P.; Giles, Matthew D.; Whittall, Jonathan P.; Gurd, Brendon J.
Summary: This study investigated whether VO2 peak is reproducible across repeated tests before (PRE) and after (POST) training, and whether variability across tests impacts how individual responses are classified following 3 weeks of aerobic exercise training (cycle ergometry). Data from 45 young healthy adults (age: 20·1 ± 0·9 years; VO2 peak, 42·0 ± 6·7 ml·min −1 ) from two previously published studies were utilized in the current analysis. Non‐responders were classified as individuals who failed to demonstrate an increase or decrease in VO2 peak that was greater than 2·0 times the typical error of measurement (107 ml·min −1 ) away from zero, while responders and adverse responders were above and below this cut‐off, respectively. VO2 peak tests at PRE (three total) and POST (three total) were highly reproducible (PRE and POST average and single measures ICCs: range 0·938–0·992), with low coefficients of variation (PRE:4·9 ± 3·1%, POST: 4·8 ± 2·7%). However, a potential learning effect was observed in the VO2 peak tests prior to training, as the initial pretraining test was significantly lower than the third ( p = 0·010, PRE 1: 2 946 ± 924 ml·min −1, PRE 3: 3 042 ± 919 ml·min −1 ). This resulted in fewer individuals classified as adverse responders for Test 3 compared to any combination of tests that included Test 1, suggesting that a single ramp test at baseline may not be sufficient to accurately classify the VO2 peak response in young recreationally active individuals. Thus, it is our recommendation that the initial VO2 peak test be used as a familiarization visit and not included for analysis.